The Impact of Vitamin D Supplementation on Patients with Essential Hypertension and Vitamin D Deficiency - Dahliana, Anita; Winnie Nirmala Santosa; Dwi Martha Aditya (International Journal of Medical Science and Clinical Research Studies, 2025)
Background: The maintenance of calcium homeostasis and bone mineralization are two important functions of vitamin D in bone health. Vitamin D deficiency is known to cause cardiovascular, musculoskeletal, and other body systems diseases. Objective: To examine how vitamin D affects hypertension in those who are deficient in it. Methods: The PubMed and Google Scholar databases are used in this investigation to conduct a literature review utilizing a narrative methodology that looks at and analyzes research findings in regional or global literature. Results: Blood pressure levels after taking vitamin D are dramatically reduced. Conclusion: Patients who are vitamin D deficient can benefit from vitamin D to treat their essential hypertension.